Maternal Healthcare Utilization and Health-Related Quality of Life among Young Pregnant Mothers Aged 10-24 Years in Eastern Uganda: A Cross-sectional Study - Nakkazi Joan; Miph Musoke; Miisa Nanyingi; Frank Pio Kiyingi; Odoki Martin (International Journal of Global Health, 2026)
Introduction Young pregnant mothers experience heightened biological, social, and economic vulnerabilities that may compromise health-related quality of life (HRQoL), especially in low-resource settings. Although maternal healthcare service utilization (MHCSU) improves clinical outcomes, evidence linking it to HRQoL among young mothers in Uganda remains limited. This study examined determinants of HRQoL among young pregnant mothers aged 10–24 years in Eastern Uganda, with emphasis on MHCSU. Methods A cross-sectional analytical study was conducted among 967 young pregnant mothers in selected districts of Eastern Uganda. The study used baseline data collected prior to randomization and implementation of any intervention. Although the WHOQOL-BREF instrument was administered in full, the present analysis utilized the global quality-of-life item (Question 1:
Keywords: Determinants